The potential for kitchen incubators to assist food-processing enterprises. (1st July 2008) - Dent, Benjamin
Kitchen incubators offer food microenterprises a fully equipped food-processing facility to rent on a part-time basis, along with business and technical advice. This significantly reduces the capital costs and risks of starting a food business. This project found that substantial capital and some operating subsidies were required to fund these incubators, while only about half their clients had aspirations for their enterprises to grow. Nonetheless, incubators fostered flexible entrepreneurial jobs in both urban and rural areas. To maximise outcomes, they should incorporate collaborative distribution. Co-location with colleges provided both access to expertise and specialist equipment, and opportunities for the facilities to be used for educational, professional and community culinary training. Given potential clients' unwillingness to travel, in rural areas an alternative approach would be to broker access to existing but underutilised facilities, supplemented by advisory services.